Le roman scout dans les années trente et le chronotope du « grand jeu » - Laurent Déom (Strenae)
While the first French boy scout novels were published in the 1910s, the 1930s became the decisive period for this type of production: certain collections were entirely devoted to it, which contributed to the construction of a boy scout sector within publishing. This development went hand in hand with the considerable increase in the number of scouts in France, especially within the Scouts de France association, some of whose leaders became famous for their literary writing. This was the case with Jacques Michel, whose first novel, L'Aventure du roi de Torla, proves to what extent the pedagogical concerns of the Scouts de France found an echo in novels. This similarity manifested in a certain number of explicit discourses, but also in particular poetic phenomena—for example, what one might call the chronotype of the "great game.” Far from being confined to the work of Jacques Michel, this chronotope holds an important place within the novelistic production developed in the Scouts de France movement of the thirties (one can look to the first novels of Serge Dalens or Jean-Louis Foncine in particular), to the point that it appears as one of the characteristic features of the paradigmatic Scout novels. These novels had such success at that time, perhaps because, among other reasons, they were among the rare works of French children’s literature, which, in the interwar period, made use of this chronotope, mixing disorientation, freedom and discreet supervision.